From Autocracy to Democracy to Technocracy An Evolution of Human Polity - Shaw, Victor N. (Cambridge Scholars Publisher, 2020)
This book explores human polity with respect to its nature, context, and evolution. Specifically, it examines how individual wills translate into political ideologies, investigates what social forces converge to shape governmental operations, and probes whether human polity progresses in focus from individual wills to group interests to social integrations. The book entertains five hypotheses. The first is commonsensical: where there are people there is politics. The second is analogous: humans govern themselves socially in a way that is comparable to how a body regulates itself physically. Th.